Understanding Sthanika Upakrama in Karna Rogas: A Traditional Approach to Ear Disorders (International Journal of Ayurveda and Pharma Research, 2024)
This article delves into the traditional Ayurvedic approach of Sthanika Upakrama in managing Karnagata Rogas, or ear disorders, through localized treatments aimed at restoring Doshic balance and alleviating related symptoms. The study explores the methodology and results of employing Sthanika Upakrama as a holistic ear health approach, highlighting its potential benefits in modern healthcare practices. Ayurvedic scholars have outlined specialized methods, such as Karna pramarjana, Karna abhyanaga, Karna poorana, and Karna dhoopana etc, which hold promise for addressing auditory impairments. Amidst a substantial burden of auditory impairment in India, these ancient interventions offer potential solutions to contemporary challenges in auditory health. The integrated approach of Sthanika Upakrama presents a comprehensive strategy to prevent and manage ear-related ailments.